Capsaicin Effect on Skeletal Muscle Nicotinic Receptor A Preliminary Study - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Capsaicin Effect on Skeletal Muscle Nicotinic Receptor A Preliminary Study